INSUFFICIENT PHYSICAL ACTIVITY AND ITS IMPACT ON NATIONAL ECONOMY AND SECURITY - Kuzņecova, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Healthy and active people not only strengthen the health of the population of Latvia, prolong life in good health, prevent premature mortality, but also make an important contribution to the economic development and security of the country. Unfortunately, Latvia ranks among the last places in a number of areas among the EU member states. Latvian Health and Fitness Association (LVFA) has adapted the “Deloitte Research” global study on the preventive impact of physical activity on the national economy to the circumstances in Latvia, revealing that the Latvian economy suffers significant losses every year due to physically inactivity among the population. Furthermore, insufficient physical fitness also affects the internal and external security of the country. Must be concluded also across the globe governments face rising healthcare costs and the increasing prevalence of lifestyle diseases. This raises questions as to how bet improve the health of populations, while keeping healthcare and security costs under control. The aim of the article is to study the impact of insufficient physical activity on the national economy and security, to recommend directions for policy development in this field, and to propose improvements of the legal framework. Analytical method, comparative method, as well as the method of qualitative and quantitative data analysis were used in the development of the article.